The Effect of Foot Massage to The Ankle Brachial Index (ABI) in DM type 2 Patients in Primary Health Care II West Denpasar - Laksmi Ida Ayu Agung (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Abstract.Diabetic foot is one of the dangerous complications of diabetes mellitus patients. More than half of lower limb amputations nontraumatik associated with diabetes such as changes in sensory and autonomic neuropathy, peripheral vascular disease, increased risk and rate of infection and healing that is not good. Vascular control is done by non-invasive vascular examinations as examination ankle brachial index, leg practice and foot massage. This study aimed to assess the effect of foot massage to the ankle brachial index (ABI) in patients with type 2 diabetes. This study is a quasi-experimental studies (pretest-posttest design). Sample consisted of 28 respondents selected by purposive sampling, divided into two groups of intervention and control groups. The data was collected by measuring the ABI pre test and post test in each group. This experiment result average value of ABI after foot massage on intervention group is 0,9879 dan the avarage value of post test ABI on control group is 0.8921 Based on Independent t-Test obtained p value (0.000) < ? (0,05) then Ha is accepted, meaning that there is effect of foot massage on ABI’s patients with type 2 DM in Primary Health Care II West Denpasar. Based on the influence of foot massage on ABI’s patients of type 2 DM the authors suggest that nurses provide foot massage intervention for minimizing the risk of diabetic foot complications